AIR MANAQIB - Nashiruddin, Nashiruddin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2019)
One of the religious programs aimed to improve Santri Al Fithrah 's spiritual potential in particular, and Jama'ah or followers of Shaykh Achmad Asrori Al-Ishaqy by General, is the Manaqiban Council, that is a religious ritual containing the recitation of pray together, Istighatsah, reading Yasin letter, Reading manaqib (Biography) of Shaykh Abdul Qodir al-jilany, then completed by the reading of the Prophet's maulid. The purpose of this event is doing tawassul with teachers in trying to get closer to Allah SWT. So kind of the activities is also called Shilaturruhiyyah. There is something interesting in the event, that is every activity of the Council Manaqiban can be ascertained that Jama'ah who follow The event surely will bring or put mineral water on surrounding with the bottle cap opened condition. Apparently, the water has own special value for them, it was proved that the water then called "Air Manaqib." This issue includes to the Humanities issue (the matter of human behavior), therefore, to reveal the matter deeply and thoroughly, then the study used qualitative method. Because Qualitative methods are more adaptable to the Environment condition. From the research findings it was found that Santri or Jama'ah of the Manaqib event assumed that the water of manaqib can be used as: (1) Media of various medications of physical diseases, (2) Facilitate labor process, (3) Supernatural protect from bad influence and as a trading master. Otherwise, the way of usage according to them is no standard method or rule, but the method frequently tobe used is by drinking. After the research was done more deeply, it was found that such behavior, the treatment uses Water media has also been carried out by some Salaf scholars even though it is not called water of manaqib, but it has same substance, namely tabarrukan Judging from the view of science (scientific), with reference to the discovery of Masaru Emoto, that the nature of water can respondan information, instruction or prayer, and water that has been received message or prayer, the quality is getting higher, it means the quality of the Manaqib water is also higher. Thus, the utilization of Manaqib water is good judged from religious or science point of view can be accounted for the truth. .